THE ROLE OF DAARUL HASANAH CHILD CULTURE HOSPITAL IN STRENGTHENING CHILDREN'S INDEPENDENT LEARNING CHARACTER - Ryan Avis Tamara; Yudi Firmansyah; Fitri Silvia Sofyan (Journal Civics And Social Studies, 2026)
This study aims to describe the role of the Daarul Hasanah Orphanage in strengthening children's independent learning character, identifying the obstacles faced, and finding solutions implemented by the orphanage to address these obstacles. This study used a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the Daarul Hasanah Orphanage plays an important role in shaping children's independent learning through routine learning habits, mentoring by administrators and foster parents, and creating a conducive learning environment. The obstacles faced include limited human resources for mentors, the diversity of backgrounds of foster children, and limited infrastructure. To overcome these obstacles, the orphanage collaborates with volunteers, implements a reward-based motivation system, improves facilities with donor support, and provides counseling services for children in need. These findings confirm that fostering children's independent learning character can be carried out effectively in non-formal social institutions through a combination of habits, motivation, and a supportive environment. This study is expected to provide theoretical contributions in the development of character education, as well as practical contributions for orphanages and related parties in designing strategies to strengthen children's independent learning in a sustainable manner.